2017
DOI: 10.18178/ijfe.3.2.107-111
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Oxidative Stress by Seluang Fish (<i>Rasbora spp.</i>) in Brain of Malnourished Rats (<i>Rattus norvegicus</i>)

Abstract: Malnutrition children have lower intelligence due to brain cells damage caused by oxidative stress. Seluang (Rasbora spp.) has the potential te reduce this problem. This study aimed to analyze the correlation between hydrogen peroxide (H 2 O 2) levels with malondialdehyde (MDA) levels in the brain of malnourished rats after administration of seluang.  This study used a posttest only with control group design. 30 white rats (Rattus norvegicus) made into malnutrition and divided into three groups, M: malnutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…The amino acid content of cysteine which has a thiol group in seluang fish can act as an antioxidant. This had been proven by a study from Triawanti et al [13] malnourished rats given seluang fish showed improvement in oxidative stress conditions. The MDA level decreased, and the enzymatic antioxidant activity was improved.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The amino acid content of cysteine which has a thiol group in seluang fish can act as an antioxidant. This had been proven by a study from Triawanti et al [13] malnourished rats given seluang fish showed improvement in oxidative stress conditions. The MDA level decreased, and the enzymatic antioxidant activity was improved.…”
Section: Discussionmentioning
confidence: 86%
“…A study by Yunanto et al proved that white rats fed with seluang fish had better spatial memory and higher PPARg and PPARa expressions compared to rats fed by standard feed [12]. Triawanti et al study had proven that seluang fish can improve the oxidative stress condition of the brain after malnutrition [13].…”
Section: Introductionmentioning
confidence: 99%
“…Rats are considered undernourished when plasma protein levels <4,7 g/dL [6]. R. norvegicus's normal protein level is 4,7e5,2 g/dL [7].…”
Section: Preparation Of Experimental Animals Malnutritionmentioning
confidence: 99%
“…After administration of low protein feeding (AIN-76A) for 8 weeks (56 days) post natal it is known that the mean rats protein level was 1.9 g/dL below the normal level which is 4.7 g/dL [7]. The average body weight after 8 weeks of low protein feeding (AIN-76A) were P1 ¼ 118.3 ± 9.83 g; P2 ¼ 74.28 ± 11.33 g; P3 ¼ 76.67 ± 5.16 g, respectively.…”
Section: Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation